Surfactant-free poly(lactide-co-glycolide) nanoparticles for improving in vitro anticancer efficacy of tetrandrine. (2nd April 2016) - Shi, Chen; Zeng, Fang; Fu, Dehao
Abstract: The objective of this study was to improve the efficacy of a natural compound tetrandrine against cancer by designing surfactant-free poly(lactic-co-glycolic acid) (PLGA) nanoparticles as drug carriers for tetrandrine. Nanoparticles were prepared from PLGA via the nano-precipitation method with or without the presence of surfactant poly(vinyl alcohol) (PVA) to encapsulate tetrandrine. Tetrandrine-loaded surfactant-free PLGA nanoparticles had an average particle size of 169.3 nm and morphology similar to the PLGA nanoparticles prepared using PVA as the surfactant. Tetrandrine-loaded surfactant-free PLGA nanoparticles could retard drug release in phosphate buffered saline (PBS) at pH 7.4 and the cumulative release of tetrandrine reached up to 68.33% over a period of 120 h. A549 cell line was used as the model cancer cells to investigate anticancer capability of tetrandrine-loaded surfactant-free PLGA nanoparticles via apoptosis assay, cytotoxicity and lysosome injury studies. The results showed that tetrandrine-loaded surfactant-free PLGA nanoparticles could effectively reduce cell viability and synergistically enhance tetrandrine-induced cell apoptosis.